Long-term hormonal treatment reduces repetitive surgery for endometriosis recurrence. Issue 2 (February 2021) - Capezzuoli, Tommaso; Vannuccini, Silvia; Mautone, Daniele; Sorbi, Flavia; Chen, Huixi; Reis, Fernando M.; Ceccaroni, Marcello; Petraglia, Felice
Abstract: Research question: How effective is medical hormonal treatment in preventing endometriosis recurrence and in improving women's clinical symptoms and quality of life? Design: This observational cross-sectional study evaluated the effects of hormonal medical treatment (progestins, gonadotrophin-releasing hormone analogues or continuous oral contraceptives) on endometriosis recurrence, current clinical symptoms and quality of life in three groups of patients: Group A ( n  = 34), no hormonal treatment either before or after the first endometriosis surgery; Group B ( n  = 76), on hormonal treatment after the first endometriosis surgery; and Group C ( n  = 75), on hormonal treatment both before and after the first endometriosis surgery. Results: Group C patients were characterized by a lower rate of endometriosis reoperation ( P  = 0.011) and a lower rate of dysmenorrhoea ( P  = 0.006). Women who experienced repetitive endometriosis surgery showed worse physical ( P  = 0.004) and mental ( P  = 0.012) status than those who received a single surgery, independent of the treatment. Conclusion: Hormonal treatments represent a valid cornerstone of endometriosis management and may be useful as an alternative to surgery, but also before surgery, to plan better, and after surgery in order to reduce the risk of recurrence. Medical counselling is very helpful in choosing the correct and individualized endometriosis treatment. In fact, the gold standard for modern endometriosis management is the individualized approach and surgery should be considered, depending on the clinical situation and a patient's symptoms.